Diversity and Conservation Status of Ornamental Fish in Bandung, West Java, Indonesia - Tri Cahyanto; Wildan Arsyad Fadly; Haryono Haryono; R. Ajeng Syahar Syahar; Epa Paujiah (Biota, 2019)
Indonesia is an area rich in biodiversity and several fish population be potential to ornamental fish development. Ornamental fish development is one of interesting commodities because it has a broad market share both locally and export. Increased demand for ornamental fish in the market leads breaders or traders who make ornamental fish as a potential commodity and its can impact on fish conservation. However, the potential of ornamental fish had not been properly recorded so that mapping needs to undertake. This study aims to know the diversity of fish which traded and the condition of business actors, especially in the Tegallega ornamental fish market, Bandung. The research was conducted through interviews and direct observations in the field from January to February 2018. The results showed that there were 55 species of fish belonging to 27 Families; the most popular fish is Goldfish (Carassius auratus). Two species including to Endangered (EN) category, one species including to Vulnerable (VU) category, 24 species including to Least Concern (LC) category, three species including to category of Data Deficient (DD), and nine species including to category of Not Evaluated (NE). This data can be used to be more information about the conditions of ornamental fish commodities for businessman, fisheries services, academics, and management strategies by goverment regarding ornamental fish.